2015
DOI: 10.1210/jc.2015-1113
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain and Progression to Type 2 Diabetes in Women With a History of Gestational Diabetes Mellitus

Abstract: Postpartum increase in BMI is significantly associated with a risk of diabetes and deterioration of metabolic phenotypes in Korean GDM women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 35 publications
(21 reference statements)
2
55
0
Order By: Relevance
“…However, this should be carefully interpreted, as individual studies did not distinguish the incidence of early postpartum diabetes (≤ 8 weeks after delivery) from that of late conversion to diabetes but only determined the average incidence after several years of follow-up in each study. Studies from Korea reported that the incidence of early postpartum diabetes (6 to 8 weeks) was higher than 10% [36,45]. This incidence rate (incidence per unit time) during the early postpartum period was much higher than the rate of ~50% of postpartum diabetes in following 5 to 10 years [7].…”
Section: Postpartum Diabetes In Women With Previous Gdmmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this should be carefully interpreted, as individual studies did not distinguish the incidence of early postpartum diabetes (≤ 8 weeks after delivery) from that of late conversion to diabetes but only determined the average incidence after several years of follow-up in each study. Studies from Korea reported that the incidence of early postpartum diabetes (6 to 8 weeks) was higher than 10% [36,45]. This incidence rate (incidence per unit time) during the early postpartum period was much higher than the rate of ~50% of postpartum diabetes in following 5 to 10 years [7].…”
Section: Postpartum Diabetes In Women With Previous Gdmmentioning
confidence: 99%
“…For this reason, a prospective cohort study was conducted in Korea by Moon et al [45] which included 418 Korean women with GDM (baseline BMI 23.3 kg/m 2 ). This study demonstrated that subjects in the highest tertile of postpartum BMI change had ~2-fold higher risk of developing diabetes compared with women in the lowest tertile (mean BMI change in each tertile, 1.6 and –1.8 kg/m 2 , respectively) [45].…”
Section: Risk Factors For Postparum Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…The etiology of gestational diabetes mellitus is not well-understood. The pathogenesis of gestational diabetes mellitus involves many complex environmental and lifestyle factors, such as pregnancies at an older age, high pre-pregnancy weight and BMI, hydramnios, a history of gestational diabetes mellitus, a history of type 2 diabetes, vaginal candida infection, and a history of gestational diabetes (Kühl, 1991;Damm, 1998;Kopp, 2005;Anna et al, 2008;Savitz et al, 2008;Sella et al, 2013;Moon et al, 2015). However, not all pregnant women exposed to certain risk factors go on to develop gestational diabetes mellitus, suggesting that hereditary factors may contribute to the occurrence of this disease.…”
Section: Introductionmentioning
confidence: 99%